Women's Access to Economic Opportunities in Serbia - World Bank (World Bank, Washington, DC, 2016)
This report focuses on better understanding the factors that influence women’s economic opportunities in particular, an area in which significant inequalities remain. Women’s economic opportunity is defined as a set of laws, regulations, and practices that allow women to participate in the workforce under conditions roughly equal to those of men, whether as wage-earning employees or as owners of businesses. As such, the report looks into the ability of women to accumulate and build-up critical endowments - education and health, and to participate in the labor market and have access to jobs. By reviewing the institutions and policies relevant to gender equality in access to economic opportunities in Serbia, the intention is also to point out necessary improvements in policies and programs that will encourage women’s participation in the workplace and thus create a more productive economy overall. The analysis mostly relies on exploiting a new dataset for Serbia, the Survey on Income and Living Conditions (SILC), together with Labor Force Survey (LFS) data. The structure of the report is as follows. The first section focuses on gaps in endowments, mostly education but with insights into health care, and labor market outcomes. The second section provides an assessment of the institutional infrastructure for promoting gender equality and analyzes policies that support female labor force participation. The report concludes with several recommendations for policy reforms that could enhance women’s access to economic opportunities in Serbia.